Field collections reveal that São Tomé is the Afrotropical island with the highest diversity of drosophilid flies (Diptera: Drosophilidae). Issue 1 (2nd January 2020) - Prigent, Stéphane R.; Lang, Michael; Nagy, Olga; Acurio, Andrea; Matamoro-Vidal, Alexis; Courtier-Orgogozo, Virginie; David, Jean R.
Summary: The Drosophilid fauna has been less investigated in the Atlantic Afrotropical islands than in the Indian Ocean. Located about 250 km from the continent, the volcanic island of São Tomé has been colonized mostly by natural means, probably by the wind, since the emergence of the island about 15 million years ago, and presumably also by anthropogenic transportation of invasive and domestic species. To date, 37 different Drosophilid species have been mentioned from São Tomé. The present work extends this list to 80 species. The genera Zygothrica, Phorticella and Hypselothyrea are newly recorded from the island. Among these 80 species, only 12 are putatively introduced by human activities, suggesting the preponderance of natural arrivals. Compared to other islands, São Tomé harbours a high diversity of drosophilids. At least 14 species are supposed to be endemic. Future molecular comparisons between the island flies and their continental relatives will probably help to identify other endemic species. The high diversity observed in São Tomé is certainly due to the large size of the island, and to the presence of vast natural altitudinal forests offering a variety of possible habitats. Further collections are likely to lead to an increase of the species list. From now, São Tomé island appears as an excellent laboratory for studying the ecology and evolution of the Drosophila model.